The History of Computer Graphics and Animations - Sharma, Surendra; Prakash Jakhar, Shyo; kumari, Ayushi; Kumari, Nikita (International Journal of Psychosocial Rehabilitation, 2020)
Computer graphics are creating and manipulating visual content using computers. It consists of 2D and 3D graphics, rendering techniques, and tools to generate images, animations, and interactive experiences. Ivan Edward Sutherland created the first computer graphic design in 1963 called Sketchpad. The process of taking sequential photos of drawings or models to give the impression that they are moving is called animation. Animations are breaking human boundaries by making it easy to depict fictional/fantastical worlds and worldly elements. Allowing us to break away from the grips of science and create unique fiction. Animations are now also a major part of the educational field as many schools are teaching students through CG and animations which makes learning much more fun and immersive. Due to their unparalleled visual experiences, computer graphics and animations have long since changed a wide range of sectors and communication. CG made it possible to create Japanese anime and cartoons for enjoyment. Incredible amazing effects, captivating environments, and distinctive characters in motion pictures and video games. Additionally, CG is greatly improving education by using interactive animations to make complex ideas look interesting and approachable. CG is used to create 3D models, visualizations, and data analysis. In more practical domains including engineering, medicine, and architecture. This improves diagnostics and decision-making increasing productivity. Computer graphics have made it possible to push beyond the limits of science, education, and creativity. CG has also encouraged innovations and fundamentally changed how we see and engage with the world. Their influence will only increase, creating a plethora of opportunities for mankind’s future.